Hope on the horizon: how pegbelfermin offers a glimmer of hope for NASH sufferers? - Mukhtiar, Sawairah; Nisha Babar; Fatima Rehan (Journal of the Pakistan Medical Association, 2023)
Madam, Non-alcoholic steatohepatitis (NASH), is described as having hepatic steatosis of >5%, inflammation, and hepatocyte damage (such as ballooning), including or excluding fibrosis¹. NASH falls under a group of liver diseases termed Non-alcoholic Fatty Liver Disease (NAFLD) varying from benign steatosis to inflammatory NASH and hepatic fibrosis. ---Continue